Experimental study and modeling of the mechanical behavior of recycled aggregates-based high-strength concrete (Fracture and Structural Integrity, 2021)
Concrete, a material of prime importance, is widely used in various works. Among the raw materials composing concrete, aggregates come first. It is widely acknowledged that the consumption of natural aggregates increases with the growth in the amount of concrete needed. It has recently emerged that concrete waste can be recycled and reused in civil engineering works after a series of treatments. Moreover, in order to protect the environment and based on the principles of sustainable development, it was considered urgent to produce a High Strength Concrete incorporating recycled materials in addition to silica fume and a high-efficiency superplasticizer. This would certainly help to establish a harmonious sustainable development that guaranties the ecological balance and environmental protection, and prevents the depletion of natural resources. This study is part of a larger research program that that seeks to recover, recycle and valorize construction and demolition wastes. The main objective sought in this article is firstly to use aggregates from demolition concrete in the manufacture of a new concrete with high mechanical and rheological performance, and secondly, to model the behavior of this type of concrete using the Finite Element Method. This modeling aims to evaluate the maximum compressive strengths and compare them with those obtained experimentally.
Keywords: High strength concrete; Recycled aggregates; Environment; Modelization; Finite element method